2021
DOI: 10.3390/nano11071677
|View full text |Cite
|
Sign up to set email alerts
|

Chelator-Free/Chelator-Mediated Radiolabeling of Colloidally Stabilized Iron Oxide Nanoparticles for Biomedical Imaging

Abstract: The aim of this study was to develop a bioimaging probe based on magnetic iron oxide nanoparticles (MIONs) surface functionalized with the copolymer (p(MAA-g-EGMA)), which were radiolabeled with the positron emitter Gallium-68. The synthesis of the hybrid MIONs was realized by hydrolytic condensation of a single ferrous precursor in the presence of the copolymer. The synthesized MagP MIONs displayed an average Dh of 87 nm, suitable for passive targeting of cancerous tissues through the enhanced permeation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Similar nanosystems reported by Papadopoulou et al, with a highly negative surface charge (−36 mV versus−40 mV in the case of [ 68 Ga]Ga-MA), seem to have more interactions with macrophages and highly accumulate in organs such as the liver and spleen but also in lungs, especially at 30 min p.i. [ 45 ]. In most cases reported, surface functionalization with a biocompatible coating displays similar in vivo biodistribution as in the case of [ 68 Ga]Ga-MAPEG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar nanosystems reported by Papadopoulou et al, with a highly negative surface charge (−36 mV versus−40 mV in the case of [ 68 Ga]Ga-MA), seem to have more interactions with macrophages and highly accumulate in organs such as the liver and spleen but also in lungs, especially at 30 min p.i. [ 45 ]. In most cases reported, surface functionalization with a biocompatible coating displays similar in vivo biodistribution as in the case of [ 68 Ga]Ga-MAPEG.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies mention the development of iron oxide nanoparticles with a condensed magnetic core, decorated with different polymers and, in some cases, with targeting moieties [ 42 , 43 , 44 , 45 , 46 ]. The condensed clustering structure refers to the in situ clustering of MIONs during crystal growth, in such a fashion that the individual MIONs adopt the same crystallographic orientation with their neighboring crystals through epitaxial aggregation [ 42 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of the cells is proportional to the color density of the purple formazan crystals. For these reasons, MTT assay can be used as an indicator for cell viability and cytotoxicity [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the existing literature, the radiochemical stability of the NMs-radiometals complex has always been investigated ex vivo as follows: after the direct (chelator-free) or indirect (typically chelator-based) chemical bond formation between the radiometals and the NMs surface, the complex is incubated in simulated body fluids (i.e., serum or PBS at 37°C) for several hours or overnight, and then the detached radiometals are collected and quantified by means of centrifugation, chromatography, or liquid chromatography ( Korany et al, 2020 ; Wang L. Z. et al, 2020 ; Papadopoulou et al, 2021 ). However, one of our work just demonstrated that some features of the particokinetics may lead to a previously underappreciated loss in the in vivo stability of radiolabeling ( Zhang et al, 2019 ).…”
Section: In Vivo Stability Of Radiolabelingmentioning
confidence: 99%